GIS-Based Area Suitability Analysis for Development Planning Purposes Campus: Case Study Banyuwangi State Polytechnic - Endi Sailul Haq, Farisqi Panduardi (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
In the context of the ecological relationship between humans and the academic environment, success in obtaining high-quality graduations influenced by the quality of the building's space system and other supporting facilities as a place for students to study. So the construction site's design becomes an essential factor to consider in the educational environment. Banyuwangi state polytechnic has not implemented and developed SIG to determine the construction site. Hence, it causes campus spatial planning problems for the future, like puddles, floods, noisy classrooms, and difficult access to each building. Banyuwangi State Polytechnic, as a twelve-year-old college in Banyuwangi, is in desperate need of regional development planning as one of the efforts to ensure the continuity of academic activities that are adequate and comfortable for students. This study aims to ?nd out the area suitability for determining Banyuwangi State Polytechnic development's best location choice. Banyuwangi State Polytechnic, located in the middle of the public road on the east side and the railway in the west to the north, causes noise levels to be a critical issue to consider to achieve a fair learning process. Area suitability assessment is a critical determinant in campus planning development. The suitability assessment is carried out through the AHP (analytical hierarchy process) model covering all land, buildings, noise levels, soil slope, road access, and availability of irrigation channels. The data obtained mapped into the Geographic Information System using Quantum GIS (QGIS) software. Land-use suitability is calculated based on criteria in the form of noise level (NL), land elevation (EL), ease of access (RA), and irrigation channel (ICA). There are 4 points obtained after discussions with the development planning unit management for alternative locations for development sites. The highest weight of the best criteria for determining location is the NL criteria of 0.566 and PSI of 0.283. The best location for development is in the second alternative location with a weight of 0,20176, followed by the third alternative location with a weight of 0,12028.